Sexual Double Standard: A Psychometric Study From a Macropsychological Perspective Among the Spanish Heterosexual Population - Gómez Berrocal, María del Carmen; Vallejo-Medina, Pablo; Moyano, Nieves; Sierra, Juan Carlos (Frontiers in Psychology, 2019)
In the context of heterosexual relationships, the sexual double standard (SDS) leads to a more negative assessment of women than men when they exhibit the same sexual behavior. This work assumes that in Western democratic societies, the individual attitude towards SDS takes different forms due to the processes of conviction regarding the social norm that exists on this matter. Therefore, the individual attitude towards SDS will depend on the person's perception of what others think about that topic. We distinguish between self-referred response, it refers to subjects 'personal endorsement of the SDS, and responses hetero-referred, subjects' perception of sexual societal double standard. This paper presents a version of the Double Standard Scale (SDSS) that assesses the subjective perception of society's support for the Sexual Double Standard (SDS). We examine its psychometric properties in a sample of Spanish population heterosexual of 1,206 individuals (50% males), distributed across three groups (18-34, 35-49, and 50 years old or older).We performed Exploratory and Confirmatory Factor Analysis. The final version consists of 18 item distributed into three factors (Acceptance for Male Sexual Shyness, Acceptance for Female Sexual Freedom and Acceptance for Traditional Double Standard). Said three-factor structure does not match with the two-factor structure of the self-referred form. Internal consistency, temporal stability and validity evidence are reported. This version of the SDSS is reliable and valid. No gender differences are found in the SDSS-H. However, the results show that the context of group membership, based on education and age, is differently associated with the response to SDSS-H. That is, higher scores are found for individuals with the highest education and for the youngest participants.. We discuss the usefulness of this measure to improve the prediction of individual attitude towards SDS, as well as, to evaluate the SDS phenomenon at a level of macropsychological analysis.